2021
DOI: 10.1136/archdischild-2020-321426
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety/tolerability of isoniazid, rifampicin and pyrazinamide in children and adolescents treated for tuberculous meningitis

Abstract: ObjectiveTo assess the pharmacokinetics and safety/tolerability of isoniazid, rifampicin and pyrazinamide in children and adolescents with tuberculous meningitis (TBM).DesignProspective observational pharmacokinetic study with an exploratory pharmacokinetic/pharmacodynamic analysis.SettingHasan Sadikin Hospital, Bandung, Indonesia.PatientsIndividuals aged 0–18 years clinically diagnosed with TBM and receiving first-line anti-tuberculosis drug dosages according to revised WHO-recommended treatment guidelines.In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
0
25
0
6
Order By: Relevance
“…This short-course, high-dose therapy has recently been added by WHO as an alternative treatment option for childhood TBM ( 41 ). Suboptimal plasma and CSF concentrations with standard doses of oral rifampin at 10–20 mg/kg/day in children with TBM have also been reported in recent pharmacokinetic studies ( 42 , 43 ), advocating the use of higher rifampin doses with further efficacy and safety evaluations.…”
Section: Discussionmentioning
confidence: 88%
“…This short-course, high-dose therapy has recently been added by WHO as an alternative treatment option for childhood TBM ( 41 ). Suboptimal plasma and CSF concentrations with standard doses of oral rifampin at 10–20 mg/kg/day in children with TBM have also been reported in recent pharmacokinetic studies ( 42 , 43 ), advocating the use of higher rifampin doses with further efficacy and safety evaluations.…”
Section: Discussionmentioning
confidence: 88%
“… 34 , 35 In order to formulate an effective therapeutic regimen, we adopted high-dose isoniazid (800mg/d) and found that its CSF concentration reached a maximum (11.57 ug/mL) 6 hours after administration, which mean about 100% brain penetration and promised an effective bactericidal activity in the brain. 29 After WGS of our patient’s CSF showed susceptibility of isoniazid, we lowered the isoniazid dose to 600 mg/d. Peripheral neuropathy is the most common toxicity from long-term use of isoniazid.…”
Section: Discussionmentioning
confidence: 99%
“…Several first-line anti-tuberculosis drugs (e.g., rifampicin and ethambutol) have poor penetration across the blood-brain and the blood-CSF barriers [63]. Rifampicin remains an essential medication for TBM [64] but standard dosing yields CSF concentrations that are below the minimal inhibitory concentration (MIC) for M. tuberculosis in a large proportion of patients, including children [65][66][67]. A recent model-based meta-analysis using emerging data from adult trials showed a strong positive correlation between rifampicin concentrations and survival, with doses of at least 30 mg/kg predicted to improve survival substantially compared to 10 mg/kg [68].…”
Section: Treatmentmentioning
confidence: 99%